The Satnami story : a thrilling drama of religious change - McGavran, Donald Anderson, 1897- (Pasadena, Calif. : W. Carey Library, 1990)
Includes bibliographical references and index.
Keywords: MISSION - INDIA - HISTORY; Mission to Satnamis, India - Church History